THE IMPACTS THE ACCURACY, RELIABILITY, AND CREDIBILITY OF LABORATORY TEST RESULTS. - Yasir Awad Ahmed, Areej Nasser Saud Alrami (Chelonian Research Foundation, 2024)
Laboratory test results play a crucial role in the field of science and medicine, providing valuable information that guides diagnosis, treatment, and research. However, the accuracy, reliability, and credibility of these results are essential to ensure the validity of conclusions drawn from them. This essay explores the impacts of accuracy, reliability, and credibility on laboratory test results, highlighting the factors that influence these qualities and the potential consequences of errors. By understanding the importance of these factors, professionals can work towards improving the overall quality of laboratory testing practices.